2021
DOI: 10.48550/arxiv.2106.04224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Online Correlated Selection

Abstract: This paper studies the online correlated selection (OCS) problem introduced by Fahrbach, Huang, Tao, and Zadimoghaddam (2020) to get the first edge-weighted online bipartite matching algorithm that breaks the 0.5 barrier. Suppose that we receive a pair of elements in each round and select one of them. Can we select with negative correlation to be more effective than independent random selections? Our contributions are threefold. For semi-OCS, which considers the probability that an element remains unselected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is shown that the naïve greedy algorithm achieves the optimal competitive ratio of 0.5 among deterministic algorithms, and the Ranking algorithm achieves the optimal competitive ratio of 1 − 1/e among random algorithms. Since then, a fruitful line of research has been established based on the one-sided arrival model, including simplifications of the analysis of Ranking [3,9,18], the vertex-weighted version [1,21], the edge-weighted version [4,7,14,15,17,27], the random arrival version [25,28], b-matching [24], and Adwords [5,8,23,29].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the naïve greedy algorithm achieves the optimal competitive ratio of 0.5 among deterministic algorithms, and the Ranking algorithm achieves the optimal competitive ratio of 1 − 1/e among random algorithms. Since then, a fruitful line of research has been established based on the one-sided arrival model, including simplifications of the analysis of Ranking [3,9,18], the vertex-weighted version [1,21], the edge-weighted version [4,7,14,15,17,27], the random arrival version [25,28], b-matching [24], and Adwords [5,8,23,29].…”
Section: Introductionmentioning
confidence: 99%